The misuse of "workload" in sports science and possible solutions - Ide, B. N.; Silvatti, A. P.; Marocolo, M.; Oranchuk, D. J.; Mota, G. R. (Strength and Conditioning Journal, 2023)
Because of fundamental mechanical misconceptions, workload is a contested and nonsensical term that has been erroneously used in sports science literature. When the term workload is used, readers may interpret the term to mean: (a) load, referring to the weight force of an object, or an external or internal force, applied in a specified direction and, when using the International System of Units (SI), the outcome measure must be reported in newtons, or (b) the amount of work performed, which should be reported in joules. Solutions consistent with the SI and using proper scientific terminology are simple and would improve the advancement and use of knowledge in sports science. During an endurance training program, exercise duration, relative or absolute mean velocity, distance traveled, and power output are manipulated. Within strength and power training programs, variables to be considered are repetitions and sets, rest period durations, and the load lifted. In team sports, performance quantification includes displacement, distance traveled, velocity, and acceleration. These physical quantities should replace the vague and inaccurate term workload. The quantification of physical performance should be accomplished using the SI for clarity of communication and seamless use across all subdisciplines of sports science.